Rural Galilee and Rapid Changes: An Investigation of the Socio-Economic Dynamics and Developments in Roman Galilee - Jensen, Morten Hørning (Biblica, 2012)
Much research on the socio-economic conditions of Galilee in the Herodian period has argued for a rapid economic deterioration amongst the rural population. This is said to have resulted in a deadly spiral of violence prompting popular protest movements of which Jesus of Nazareth became the most renowned. Other investigations, however, paint a much more lenient picture of Galilee being under only a moderate development. This article outlines the problem at hand in the research, suggests a methodology for further development and applies this to new archaeological material emerging from excavations in Galilee and the textual material available.